2019
DOI: 10.21276/aanat.2019.5.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Case Based Learning with Conventional Teaching in Anatomy

Abstract: Introduction: Case based learning (CBL ) is an efficient method of making dry subject like anatomy interesting and student centered. Subjects and Methods: A group of students of 1 st MBBs were taught by CBL while the other group was taught by conventional teaching methods and both the groups were assessed for their performance. Results: Students had a better understanding of the topic on being taught by CBL. Conclusion: CBL is a good approach to teach anatomy to medical students as it makes the subject quite l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
3
1
0
Order By: Relevance
“…The current study showed that students considered PBL more effective in understanding the concepts of anatomy compared to CTM, which was in line with studies conducted in a variety of settings globally [10][11][12][13] .…”
Section: Discussionsupporting
confidence: 89%
“…The current study showed that students considered PBL more effective in understanding the concepts of anatomy compared to CTM, which was in line with studies conducted in a variety of settings globally [10][11][12][13] .…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that CBL is an effective teaching-learning method helping the students to build on prior knowledge, integrate the knowledge, and consider an application to future situations. Similar observations were reported by Shaifaly et al [ 18 ] and Nair et al [ 19 ] in Anatomy, and Singhal et al [ 20 ] and Blewett et al [ 21 ] in Microbiology. The mean difference between post-session test and retention test scores is higher in the CBL group.…”
Section: Discussionsupporting
confidence: 89%
“…The current cross over study between two groups of pharmacy practice students equally exposed to both didactic lectures and casebased pedagogy in musculoskeletal system diseases and drug therapy revealed significantly higher learning, observations of which are similar to CBL studies performed in medical students [49][50][51][52].…”
Section: Discussionsupporting
confidence: 66%